EXPLORING ENGLISH TEACHERS’ ONLINE LEARNING READINESS POST-PANDEMIC: TECHNICAL AND PEDAGOGICAL PERSPECTIVE - Sri Astuti; Muhammad Fathur Rahman Khalik (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
The COVID-19 pandemic accelerated the shift to online learning, requiring teachers to adapt quickly to digital platforms. In the post-pandemic era, their readiness to sustain online teaching has become a critical issue in education. This study aims to examine the readiness of high school English teachers to implement online learning in the post-pandemic context, with particular attention to technical and pedagogical dimensions. Employing an explanatory sequential mixed-methods design, the quantitative data were collected from 39 teachers through a survey, followed by qualitative data obtained from semi-structured interviews with six teachers. The findings indicate that teachers demonstrated high level of both technical and pedagogical readiness, with no statistically significant differences observed based on gender. The interview results further revealed several factors supporting teacher readiness, including the perceived effectiveness of technology and teachers’ knowledge and skills. Conversely, several hindering factors were also identified, such as lack of ICT infrastructure and technical problems, students’ behavior, and negative perceptions of online learning. These findings underscore the importance of continuous training focused on digital pedagogy and the need for policy and infrastructure support to enhance teachers’ readiness in facing post-pandemic learning transformation.